Non-sentinel axillary tumor burden applying the ACOSOG Z0011 eligibility criteria to a large routine cohort - Riedel, Fabian; Heil, Jörg; Feißt, Manuel; Sohn, Christof; Schütz, Florian; Golatta, Michael; Hennigs, André (Breast cancer research and treatment, 2019)
Purpose: In the ACOSOG Z0011 trial, patients with primary breast cancer (BC) and 1-2 tumor-involved sentinel lymph nodes (SLN) undergoing breast-conserving surgery gained no benefit from completing axillary lymph node dissection (cALND). This paper reports cALND rates performed in clinical routine on patients who would meet the Z0011 criteria. Further, patients still received cALND were analyzed concerning the number of non-sentinel metastases (NSM) to estimate occult axillary tumor burden. Methods: Data were retrospectively analyzed from patients treated in 179 German breast centers between 2008 and 2015. Time-trend rates were determined for cALND regarding the presence of axillary macrometastases or micrometastases. Descriptive statistics were used to report the number of NSM depending on the number of SLN removed, tumor-involved SLN, tumor stage (pT1-2), and immunohistochemical subtype. Factors associated with NSM were identified using multivariable logistic regression. Results: Altogether, data for 188,909 patients were available, of whom 13,741 (7.3%) were identified eligible for the Z0011 criteria. For these patients, the cALND rate for macrometastases declined from 96.4% in 2008 to 49.7% in 2015, for micrometastases from 86.7 to 5.9%. In total 9773 patients still received cALND, 33.4% of whom had NSM. The NSM rates were: 38.8% for pN(1/1sn), 28.6% for pN(1/2sn), and 50.9% for pN(2/2sn). Hormone receptor (HR) positive/HER2+ showed the highest NSM rate (41.6%), HR−/HER2− the lowest rate (29.4%). Conclusions: The rate of cALND for ACOSOG Z0011 eligible patients has decreased substantially in routine care in our nationwide cohort. Our data reveal a relatively high prevalence of additional axillary NSM tumor burden.
Gesehen am 29.08.2019